Do spatial dependence and market power matter in the diversification of cooperative banks?. (22nd June 2022) - Algeri, Carmelo; Forgione, Antonio F.; Migliardo, Carlo
Abstract: This study examines the determinants of cooperative banks' diversification proclivity, with consideration of the spatial dependence effect. The empirical analysis demonstrates that Italian cooperative banks operate as a network with significant spillover effects that should not be ignored. Indeed, local banks compete in the same market segment, and any shift in their diversification strategy has a cascading effect on neighbouring cooperative banks as a result of customer migration. Finally, we observe that an increase in bank market power results in a decline in local bank lending activity.